المشكلات الصفية التي تواجه معلمي المرحلة الابتدائية الجدد بمدارس مدينة أفلو - شرفي, بوبكر; محمد, داودي (Université de M'sila, 2020)
ملخص :تهدف الدراسة الحالية إلى التعرف على المشكلات الصفية التي تواجه معلمي المرحلة الابتدائية الجدد بمدارس مدينة أفلو، واستقصاء علاقة تلك المشكلات بجنس المعلم ومادة تدريسه والطور الذي يدرسه، وتكون مجتمع الدراسة من جميع معلمي التعليم الابتدائي الجدد بمدينة أفلو، والذين لا تزيد سنوات خدمتهم عن ثلاث سنوات، وبلغت عينة الدراسة 83 معلما ومعلمة، تم اختيارهم عشوائيا، ولجمع المعلومات اللازمة تم بناء استبانة اشتملت على 45 مشكلة صفية موزعة على خمسة مجالات . وأظهرت نتائج الدراسة أن أهم المشكلات الصفية التي يعاني منها المعلم الجديد، هي مشكلات تتعلق بالتلاميذ، ثم يليها مشكلات تتعلق بالمناهج، ثم مشكلات تتعلق بأولياء التلاميذ، ثم مشكلات تتعلق بالمعلم وأخيرا مشكلات تتعلق بالبيئة المدرسية، كما أظهرت النتائج عدم وجود فروق ذات دلالة احصائية بين المشكلات الصفية تعزى إلى جنس المعلم، ووجود فروق ذات دلالة احصائية بين متوسطات المشكلات تعزى إلى مادة تدريس المعلم وطور تدريسه. الكلمات المفتاحية: المشكلات الصفية، معلم المرحلة الابتدائية الجديد Abstract : This current study aims at finding out class issues that are encountered by the new primary schools teachers in Aflou and investigating/questioning the relationship between these issues and the teachers' gender, the teaching material and the stage in which he or she is in charge of. The whole study is concerned with all the newest primary teachers in Aflou city whose experience is not more than 03 years of service, and this study sample reaches 83 teachers of both genders(males and females) who have been selected randomly. In order to gather the necessary information, a questionnaire was made that includes 45 class issues which were distributed on five main fields. The study results show that the new primary teachers suffer from the issues related to pupils (learners). Then, the ones related to syllabuses/curriculum. After that, come the issues related to pupils' parents. Next, it comes the ones related to the teachers themselves and finally the issues linked to the schooling environment. Also these results show that there are no statistical indication of differences between the classes issues linked to the teacher's gender, also there are no statistical differences between the issues and teachers ’gender but there are statistical differences between averages related to the teaching subject, the teacher itself and the stages of teaching. Key words: the class issues. the new teacher of primary school résumé : Cette étude actuelle vise à reconnaitre les problèmes de classe que rencontrent les nouveaux enseignants du cycle primaire de la ville d’Aflou, ainsi de s’interroger sur la relation de ces problèmes avec le sexe de l’enseignant, de sa matière d’enseignement et du cycle qu’il enseigne. Le groupe de l’étude se compose de tous les nouveaux enseignants de l’école primaire dans la ville d’Aflou, qui n’ont pas exercé plus de trois ans, l’échantillon est de 83 enseignant et enseignante, choisis aléatoirement, et pour collecter les informations nécessaires on a conçu un sondage de 45 problèmes répartis sur cinq domaines. Les résultats montrent que les problèmes de classe les plus importants dont le nouveau enseignant souffre sont liés aux élèves, puis viennent ceux liés aux programmes, ensuite ceux liés aux parents et ceux liés à l’enseignant et finalement des problèmes liés à l’environnement scolaire. Les résultats ont montré aussi qu’il n y a aucune différence de nature statistique entre les problèmes de classe dus au sexe de l’enseignant, mais qu’il y a des différences statistiques entre les moyennes des problèmes dus à matière de l’enseignant et de son cycle d’enseignement. Mots clés : les problèmes de classe, le nouvel enseignant du cycle primaire
Keywords: الكلمات المفتاحية: المشكلات الصفية، معلم المرحلة الابتدائية الجديد